Multifocal Cerebral Microinfarcts Modulate Early Alzheimer’s Disease Pathology in a Sex-Dependent Manner - Lecordier, Sarah; Pons, Vincent; Rivest, Serge; ElAli, Ayman (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) constitutes a major cause of dementia, affecting more women than men. It is characterized by amyloid-β (Aβ) deposition and neurofibrillary tangles (NFTs) formation, associated with a progressive cognitive decline. Evidence indicates that AD onset increases the prevalence of cerebral microinfarcts caused by vascular pathologies, which occur in approximately half of AD patients. In this project, we postulate that multifocal cerebral microinfarcts decisively influence early AD-like pathology progression in a sex dependent manner in young APP/PS1 mice. For this purpose, we used a novel approach to model multifocal microinfarcts in APP/PS1 mice via the sporadic occlusions of the microvasculature. Our findings indicate that microinfarcts reduced Aβ deposits without affecting soluble Aβ levels in the brain of male and female APP/PS1 mice, while causing rapid and prolonged cognitive deficits in males, and a slow and transient cognitive decline in females. In male APP/PS1 mice, microinfarcts triggered an acute hypoperfusion followed by a chronic hyperperfusion. Whereas in female APP/PS1 mice, microinfarcts caused an acute hypoperfusion, which was recovered in the chronic phase. Microinfarcts triggered a robust microglial activation and recruitment of peripheral monocytes to the lesion site and Aβ plaques more potently in female APP/PS1 mice, possibly accounting for the reduced Aβ deposition. Finally, expression of Dickkopf-1 (DKK1), which plays a key role in mediating synaptic and neuronal dysfunction in AD, was strongly induced at the lesion sites of male APP/PS1 mice, while its expression was reduced in females. Our findings suggest that multifocal microinfarcts accelerate AD pathology more potently in young males compared to young females independently upon Aβ pathology via modulation of neurovascular coupling, inflammatory response, and DKK1 expression. Our results suggest that the effects of microinfarcts should be taken into consideration in AD diagnosis, prognosis, and therapies.